Determination of Fill Factor and Efficiency in Solar Cell Type (99 × 69) mm2 with Arduino Uno R3 Based Drive assisted by Logger Pro 3.14.1 - Hamzah, Hamzah; Toifur, Moh.; Ishafit, Ishafit (Indonesian Review of Physics (IRiP), 2019)
Abstrak- The study about fill factor and efficiency solar cell have been done with an automatic drive machine that rotates the surface of the solar cell following the movement of the light source from 0° up to 90° compared without automatic drive.  The test results are then implemented to determine the fill factor and efficiency in variations in light intensity. In this study, polycrystalline solar cell type (99 × 69) mm2, the Philips 100W/220V light bulb at a distance of 18 cm and the driving machine is controlled through an Arduino Uno R3 microcontroller. Data acquisition of current and voltage is carried out with the help of DCP-BTA current and VP-BTA voltage probes that are connected to the mini labquest transducer and displayed to a computer through loggerpro software. The result show that it has been successfully designed an automatic driver of a solar panel (99 × 69) mm2  with an Arduino Uno R3 microcontroller and a logger pro software as data acquisition software. The using solar cell automatically driven can improve the accuracy and precision of current and voltage readings so the fill factor might be increased up to 10% while the efficiency of solar cells does not change. Variations in light intensity can increase the fill factor and efficiency of solar cells. Fill factor and efficiency have an exponentially relationship to light intensity.